Perlindungan Hukum Merek Dagang Asing Dalam Kasus The Cheesecake Factory - Utami, Deasy Prasetyo (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Well-known marks are associated with high reputation and value, so its synonymous with attractive designs and easy to remember with high quality products/services. In addition, the brand owner has invested to built the brand became famous. This article discusses American cakes company, namely The Cheesecake Factory, had similarities with cakeshop in similar fields in Indonesia. Intelectual Property Rights, including trademarks, certainly plays a very important role in trade because it has a high economic value. As a member of the WTO that participated in ratifying the TRIPs agreement in 1995, a trademark that is a reproduction of a pre-existing mark, imitation, or even just a mere translator as stated in article 6 bis of the Paris Convention, must be rejected or its registration cancelled. Trademark protection in Indonesia is regulated in Law no. 15 of 2001 which was repealed and corrected by Law no. 20 of 2016, but in reality there are still disputes against foreign trademark owners which cannot be fully protected. This article will look at the practice of a lawsuit for trademark infringement that occurred in 2013 between The Cheesecake Factory and De Silva U Chandra but was declared defeated due to premature plaintiffs, as well as solutions to this problem in the future in the form of protecting foreign trademarks and outreach to perpetrators business regarding Intelectual Property Rights.